(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This study looks at the distribution of population in Sindhudurg and Ratnagiri districts of Maharashtra state. Literacy rate is a gauge of social progress and educational achievement in a community. The study examines the spatial distribution of the population at tehsil level in the district. When compared to inland places, coastal regions especially those with ports or fishing industries may have a comparatively greater level of economic growth. Both districts rely heavily on agriculture, which includes the production of rice, mangoes, cashew nuts, and other crops. While educational attainment varies by location, metropolitan areas often have more access to education and higher enrollment rates than rural ones. Overall, poverty, access to essential services, and environmental sustainability may still be problems in some parts of the Ratnagiri and Sindhudurg districts, despite the fact that other regions may be quite well-developed with decent infrastructure and economic prospects. The present study examines spatio- temporal changes of Ratnagiri and Sindhudurg district as per the 2001 and 2011 census data.